Bibliometric analysis of neutrophil extracellular traps induced by protozoan and helminth parasites (2008–2024) - Tamara Muñoz-Caro; Elvira M. Saraiva; Rafael M. Mariante (Frontiers in Immunology)
IntroductionParasitic diseases pose a significant global public health challenge, affecting billions of people and causing substantial economic losses in livestock and poultry. In the fight against these infections, neutrophils play a crucial role, employing various strategies, including the release of neutrophil extracellular traps (NETs). Recent studies have made significant progress in understanding NETs triggered by protozoa and helminths. However, a comprehensive bibliometric analysis that compiles these findings and identifies research hotspots and trends in this field is still lacking.MethodsWe utilized the Web of Science Core Collection and Scopus databases to retrieve original articles on NETs induced by protozoa and helminths. After screening, the data was transferred to the visualization tools VOSviewer, Biblioshiny, and CiteSpace for analysis.ResultsOur study included 159 original articles published in 69 journals, involving 909 authors from 270 institutions across 41 countries. Germany and Brazil have made the most significant contributions to the research on NETs and parasites, accounting for 45 and 32 publications, and 1,495 and 1,342 citations, respectively. Carlos Hermosilla and Anja Taubert (Justus Liebig University Giessen, Germany), and Elvira Saraiva (Federal University of Rio de Janeiro, Brazil), are leaders in the field, both in terms of publication output and citations. Frontiers in Immunology has consistently and significantly impacted the field, and an article in the Proceedings of the National Academy of Sciences of the United States of America providing the first direct evidence of NETs release in response to a parasite is by far the most cited. Current research focuses on malaria, Toxoplasma gondii, Besnoitia besnoiti, nematodes, and the mechanisms of NETs production and their effects on parasites and host cells. Emerging trends include therapeutic targeting of NETs and comparative studies across different host and parasite species.ConclusionThis study offers a comprehensive overview and visual analysis of NETs and parasites, highlighting key areas for future research.